CNN Applications in Dermal Lesion Segmentation: Progress in Precision Diagnosis - Dr. R. Prema; Sai Samarth Saketh Vuppaladhadium; Sreesa Sarma Panguluru (International Journal of Formal Sciences: Current and Future Research Trends, 2024)
Early identification of skin conditions, particularly skin cancer, is vital for enhancing treatment outcomes. Advanced technologies, such as Convolutional Neural Networks (CNNs), have significantly improved the accuracy and speed of skin lesion diagnosis. CNNs analyze medical images to identify and categorize skin lesions with impressive accuracy [1], frequently detecting early-stage cancer that might otherwise go unnoticed by healthcare professionals. This automation results in faster, more consistent diagnoses, reducing wait times and facilitating timely treatments.